Answers

2014-05-14T13:40:25+05:30
(4x2+5y2-x)-2xy
-16x²y-20xy²+2x²y
1 5 1
  • Brainly User
2014-05-14T14:52:05+05:30
Solution : (4x2+5y2-x) * (-2xy) =(4x2)*(-2xy) + (5y2)*(-2xy) - x *(-2xy) =( 8x )* (-2xy ) + (10y)*(-2xy) + 2x^2y = -16x^2y - 20xy^2 + 2x^2y = - 14x^2y - 20xy^2 Hope You Understand!
0
4 nd 2 how can u multiplied? its x power of 2 or x under the 2
oops I think it was not the x raised by .. thats is why I solved accordingly
Solution : (4x2+5y2-x) * (-2xy)
= (4x2) *(-2xy ) + (5y2)*(-2xy ) - x*(-2xy)
= - 8x3y - 10xy3 + 2x2y
or -8x^3y - 10xy^3 + 2x^2y
Hope You Understood the Solution .
Thank You !!
yes now your ans is right.........